The Relationship Between Macronutrient Intake and Stunting Among Children Aged 1–2 Years: Quantitative and Qualitative Approaches - Intan Silvia Nesva; Delmi Sulastri; Vaulinne Basyir (Masters Program in Public Health, 2025)
Background: Stunting among children aged 1–2 years remains a critical public health concern in Indonesia, particularly during the vital 1,000-day window of child development. This study aimed to analyze the relationship between macronutrient intake and stunting using a mixed-methods approach. Subjects and Method: This was a sequential explanatory mixed-methods study conducted from February 2024 to May 2025 at Community Health Center Dadok Tunggul Hitam, Padang City. The quantitative component employed a case-control design involving 66 children aged 1–2 years, divided equally into stunted (cases) and non-stunted (controls) groups. Sampling was conducted purposively for cases and by simple matching for controls. The independent variables were intake of carbohydrates, proteins, and fats; the dependent variable was stunting, defined using WHO growth standards. Macronutrient intake was assessed via a 24-hour recall. Data were analyzed using Chi-square tests to determine associations, and Odds Ratios (OR) with 95% Confidence Intervals (CI) were reported. The qualitative phase included interviews with mothers, health workers, and community volunteers, analyzed thematically using NVivo 12. Results: Children with inadequate carbohydrate intake were significantly more likely to be stunted (OR=3.50; 95% CI=1.27 to 9.64; p=0.015). No statistically significant associations were found for protein intake (OR=2.60; 95% CI=0.91 to 7.44; p=0.074) or fat intake (OR=2.44; 95% CI=0.89 to 6.70; p=0.082). Qualitative findings revealed barriers such as loss of appetite during illness, preference for snacks, food aversions, and limited maternal knowledge and resources, all of which contributed to inadequate macronutrient intake. Conclusion: Inadequate carbohydrate intake was significantly associated with stunting in children aged 1–2 years. Contextual factors such as eating behavior and parental feeding practices further influenced nutritional outcomes. Interventions should address both dietary intake and behavioral barriers within families.